2013
DOI: 10.2139/ssrn.2277355
|View full text |Cite
|
Sign up to set email alerts
|

Futures Price Volatility in Commodities Markets: The Role of Short Term vs Long Term Speculation

Abstract: Futures price volatility in commodities markets:The role of short term vs long term speculation Abstract: This paper evaluates how different types of speculation affect the volatility of commodities' futures prices. We adopt four indexes of speculation: Working's T, the market share of non-commercial traders, the percentage of net long speculators over total open interest in future markets, which proxy for long term speculation, and scalping, which proxies for short term speculation. We consider four energy co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0
10

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 22 publications
2
7
0
10
Order By: Relevance
“…Our results imply that speculation does contribute to greater uncertainty in the market regarding short‐term return developments in the form of volatility clusters. This is in line with earlier findings of Streeter and Tomek () and Manera et al (), who also find that the speculation ratio is a driver of volatility. However, as implied by the insignificant estimates for the speculation parameters in the mean equation, these effects only pertain to the short term, beyond which speculators do not appear to alter return dynamics.…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…Our results imply that speculation does contribute to greater uncertainty in the market regarding short‐term return developments in the form of volatility clusters. This is in line with earlier findings of Streeter and Tomek () and Manera et al (), who also find that the speculation ratio is a driver of volatility. However, as implied by the insignificant estimates for the speculation parameters in the mean equation, these effects only pertain to the short term, beyond which speculators do not appear to alter return dynamics.…”
Section: Resultssupporting
confidence: 93%
“…Other measures of speculative activity, which have, for example, been used in Manera et al (, ), are the long‐only, the short‐only, and the net‐long share of speculators. We denote these three shares by Stl,Sts,Stnl and define them as Stl=SLtMOIt, Sts=SStMOIt, and Stnl=SLtSStMOIt. For each of these alternative speculation measures, we construct the regime dummy series of high‐speculation regimes analogously to the method described above and repeat the main regression accordingly.…”
Section: Robustness Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Discussing several empirical also justify that investments of agricultural futures exchange are one of the factors contributing to the permanent increase in food price volatility (Gilbert 2010, Robles et al, 2009Boonyanuphong and Sriboonchitta, 2014). Manera et al (2013) used GARCH models and found that speculation significantly affected the volatility of returns. Manera et al (2013) further explained that short term speculation would cause a positive impact while long term speculation generally gave an negative effect significant on volatility for energy products (such as crude oil, heating oil, gasoline, and natural gas) and non-energy commodities such as cocoa, coffee, corn, oats, soybean oil, soybeans, and wheat over the period of 1986-2011.…”
Section: Literature Reviewmentioning
confidence: 99%